Characterisation of yeast flora isolated from an artisanal Portuguese ewes’ cheese - Pereira-Dias, S. (2019)
The evolution of the yeast flora was studied for an artisanal semi-hard ewes’ cheese made from raw milk. Mean log10 yeast counts per gram of cheese body ranged from 2.7 to 6.4, with the higher counts observed after a ripening period of 30 days. The yeast population decreased thereafter and, at the end of curing process, reached values similar to those of the beginning. A total of 344 yeasts strains were randomly isolated from the curd and cheese body during the 60 days long ripening period. Esterase activity was common to almost all isolates (98%) while proteolysis was observed in 12% of the total yeast population. The proportion of strains with positive glucose fermentation increased from 21% in the curd to 75% at the end of the ripening period. A total of 150 isolates representative of the physiological characteristics tested were examined with the API ID 32C system showing different degrees of quality of identification. Only 15% of the strains (23 isolates) were excellently identified being assigned to the species Candida zeylanoides. The most frequent species appeared to be Debaryomyces hansenii (anamorph Candida famata) and Candida intermedia. These two species amounted to 9% of the yeasts in the curd increasing to 86% at the end of the ripening period.